Backbeard : pirate for hire - McElligott, Matthew (New York : Walker & Co. : Distributed to the trade by Holtzbrinck Publishers, 2007)
When the Pirate Council tells Backbeard that he must stop wearing colorful clothing and look more fearsome, he decides to quit being a pirate and get a job on shore, if only he can find work that matches his particular skills.
A Junior Library Guild selection
Keywords: Pirates -- Juvenile fiction; Job hunting -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Humorous stories -- Juvenile fiction; Humorous stories